The effect of market intervention policy through capping rate on credit growth - EC, Anung Herlianto; Sofilda, Eleonora; Hamzah, Muhammad Zilal; Ginting, Ari Mulianta (Penerbit Universiti Kebangsaan Malaysia, 2020)
This research aims to analyze the impact of capping policy on the credit growth in the banking sector and the potential risk of insolvency. We use the dynamic panel data method on Indonesian data over January 2006 - November 2018. The results shows that monetary policy through reference interest rate (BI Rate) maintains the rate stability under normal conditions. However, in a state of shock, it shows that the policy was no longer effective in reducing the interest rate that deviates market far above the BI Rate. Therefore, a more ‘repressive’ policy is needed for the economy to continue to grow. Furthermore, the results show a policy mix between macroprudential (Central Bank) and micro-prudential (Financial Services Authority) authorities through the interaction between the BI Rate and capping. This is effective for maintaining interest stability in supporting target credit growth and minimizing risk of insolvency. The results also show that the direct interaction between macroprudential regulation and micro-prudential policy contribute to reducing the occurrence of credit shocks. Therefore, the coordination mechanism between BI and Financial Services Authority in determining interest rates needs to be regulated in a ‘rigid’ manner, in order to create synergies between monetary targets and macroeconomic conditions.